Wage effects of non-wage labour costs - María Cervini Plá; Xavier Ramos; José Ignacio Silva (Institute for the Study of Labor (IZA), 2010)
We study short- and long-term wage effects of two important elements of non-wage labour costs: firing costs and payroll taxes. We exploit a reform that introduced substantial reduction in these two provisions for unemployed workers aged less than thirty and over forty five years. Theoretical insights are gained with a matching model with heterogeneous workers, which predicts an ambiguous effect on wages: firing costs are expected to increase wages, because they increase the bargaining power of workers, while the effect of payroll taxes is negative. Difference-in-differences estimates, which account for the endogeneity of the treatment status, suggest that decreased firing costs and payroll taxes have a positive overall short-term effect on wages - and also on unemployment. We find larger effects for older than for younger workers and for men than for women. Calibration and simulation of the model shows that about fifty percent of the predicted cumulative increase on wages takes place during the first year of the reform. Our simulations also show that the increase in wages is mostly due to the reduction in payroll taxes, while the overall effect of firing costs is nil because direct and indirect effects of firing costs offset each other.
Keywords: C23; D31; J31; 330; Dismissal costs; payroll tax; evaluation of labour market reforms; difference-in-difference; matching model; Spain; Lohnbildung; Kündigungsschutz; Kosten; Lohnsummensteuer; Reform; Wirkungsanalyse; Lohn; Beschäftigungseffekt; Spanien